The role of radiotherapy as salvage and/or consolidation treatment in relapsed/refractory and high‐risk diffuse large B‐cell lymphoma. (6th June 2018) - Grignano, Eric; Laurent, Jérémy; Deau, Bénédicte; Burroni, Barbara; Bouscary, Didier; Kirova, Youlia M.
Abstract: Objective: Many salvage therapies have been proposed for relapsed/refractory (R/R) diffuse large B‐cell lymphomas or for consolidation in the case of suboptimal response. Radiotherapy (RT) is one modality of salvage therapy, but its place is currently not well defined. Method: This study reports a retrospective review of patients receiving unplanned radiotherapy for R/R diffuse large B‐cell lymphoma (DLBCL) or primary mediastinal B‐cell lymphoma (PMBCL), or as consolidation therapy after second‐line chemotherapy, treated in our hospital. Results: Fifty‐one patients with a median age of 53.5 years [19‐89] were selected. The histologic type was DLBCL in 35 cases (68%), PMBCL in 8 cases (16%), and secondary transformed NHL in 8 cases (16%). Median aaIPI was 1 [0‐4], and 17 patients (33%) had a high tumor burden (bulky disease). Sixteen patients (31%) were irradiated for a response considered to be insufficient, 18 patients (36%) were refractory, and 17 patients (33%) had relapsed. Patients were irradiated with a median dose of 40 Gy [15‐44], 29 (57%) by a conformal 3D technique and 22 (43%) by tomotherapy. With a median follow‐up of 36 months [1.0‐127.8] after irradiation, 5‐year progression‐free survival (PFS) and overall survival (OS) were 62% and 72%, respectively. In multivariate analysis, adverse factors associated with PFS and OS in our cohort were age >70 years (HR = 5.06, P  = .02) and post‐RT relapse (HR = 12.24, P  = .002), whereas favorable factors were number of lines of chemotherapy <3 (HR = 0.02, P  = .03) and bulky disease (HR = 0.02, P  = .009). Conclusion: Due to its low toxicity and ease of use, radiotherapy should therefore remain an available option in patients with R/R DLBCL or as consolidation therapy in patients with high‐risk disease, mostly in patients with chemo‐sensitive disease or bulky disease.